Effects of intestinal flora on pharmacokinetics and pharmacodynamics of drugs. (3rd April 2023) - Džidić-Krivić, Amina; Kusturica, Jasna; Sher, Emina Karahmet; Selak, Nejra; Osmančević, Nejra; Karahmet Farhat, Esma; Sher, Farooq
Abstract: Gut microbiota is known as unique collection of microorganisms (including bacteria, archaea, eukaryotes and viruses) that exist in a complex environment of the gut. Recently, this has become one of the most popular areas of research in medicine because this plays not only an important role in disease development, but gut microbiota also influences drug pharmacokinetics. These alterations in drug pharmacokinetic pathways and drug concentration in plasma and blood often lead to an increase in the incidence of toxicological events in patients. This review aims to present current knowledge of the most commonly used drugs in clinical practice and their dynamic interplay with the host's gut microbiota as well as the mechanisms underlying these metabolic processes and the consequent effect on their therapeutic efficacy and safety. These new findings set a foundation for the development of personalized treatments specific to each metabolism, maximizing drugs' therapeutic effects and minimizing the side effects because they are one of the major limiting factors in treating patients.